The prince and the pauper - Twain, Mark (Oxford University Press; Karachi, 2005)
Part of an extension to the Oxford Reading Tree TreeTops range, this work presents life in the Tudor times for rich Prince Edward and poor Tom. It offers a comparison of 2 boys born on the same day, but world's apart.